Karakterisasi Endapan Mangan Di Daerah Oelnunu, Kabupaten Timor Tengah Selatan, Provinsi Nusa Tenggara Timur - Pattimura, Nasya Syahnur; Napoh, Meinardi; Ratumanan, Ratih C F; Gultom, Rimawanto (Mataram University, 2025)
This study aims to characterize manganese deposits in the Oelnunu area, Polen District, Timor Tengah Selatan Regency, East Nusa Tenggara Province, using petrographic and geochemical analysis through X-Ray Fluorescence (XRF). The XRF results show that sample TTS-D has a very high Mn content (58.02% Mn and 74.91% MnO), along with low Fe, SiO2, and Al2O3 contents, indicating an economically viable manganese mineralization zone. Meanwhile, samples TTS-A, TTS-B, and TTS-C exhibit low Mn content with a dominance of silicate and iron elements. Petrographic analysis of TTS-D identified a dominance of opaque minerals (70%), interpreted as pyrolusite or manganite, along with secondary quartz in granular and radial fan forms (30%). The granular texture, uniform fracturing, and vein quartz support the formation of the deposit through supergene processes and tropical weathering. These findings are consistent with the lateritic manganese deposit model commonly found in tropical regions (Idrus et al., 2013; Sufriadin et al., 2015; Guo et al., 2024). This study confirms the economic potential of manganese deposits in the Oelnunu area as a target zone for further exploration.